Results of endovascular aortic arch repair using the Relay Branch system. (6th May 2021) - Czerny, Martin; Berger, Tim; Kondov, Stoyan; Siepe, Matthias; Saint Lebes, Bertrand; Mokrane, Fatima; Rousseau, Herve; Lescan, Mario; Schlensak, Christian; Andic, Mateja; Hazenberg, Constatijn; Bloemert-Tuin, Trijntje; et al.
Abstract:  : OBJECTIVES: Our goal was to evaluate results of endovascular aortic arch repair using the Relay Branch system. METHODS: Forty-three patients with thoracic aortic pathology involving the aortic arch have been treated with the Relay Branch system (Terumo Aortic, Sunrise, FL, USA) in 10 centres. We assessed in-hospital mortality, neurological injury, treatment success according to current reporting standards and the need for secondary interventions. In addition, outcome was analysed according to the underlying pathology: non-dissective disease versus residual aortic dissection (RAD) (defined as remaining dissection after previous type A repair, chronic type B aortic dissections). RESULTS: In-hospital mortality was 9% (0% in patients with RAD). Disabling stroke occurred in 7% (0% in patients with RAD); non-disabling stroke occurred in 19% (7% in patients with RAD). Early type IA and B endoleak formation occurred in 4%. Median follow-up was 16 ± 18 months. During the follow-up period, 23% of the patients died. Aortic-related deaths were low (3% in patients with RAD). CONCLUSIONS: The results of endovascular aortic arch repair using the Relay Branch system in a selected patient population with regard to technical success are good. In-hospital mortality is acceptable, the number of disabling strokes is low and technical success is high. Non-disabling stroke is a major concern, and every effort has to be taken to reduce this to a minimum. The best outcome is seen in patients with underlying RAD. Finally, more data are needed.